Senteza Kajubi's philosophy of widening accessing to higher education and its implications for research and development in Uganda - Mande, Wilson Muyinda (Nkumba Business Journal, 2010)
This paper provides an analysis of the implications of Professor Senteza Kajubi's philosophy of widening access to higher education for research and development. The thesis of this paper is that according to Senteza Kajubi, access to higher education should be widened because it leads to research which in turn contributes to development. Without research in medicine, agriculture, business, technology the development that African countries yearn for will be unattainable and elusive. The contents of this paper include a terse biography of Senteza Kajubi highlighting his role in higher education policy formulation and leadership. Access to higher education in Uganda is analysed and it is clearly shown that less about 7% of students who qualify to access higher education actually join universities in the country. Senteza Kajubi's philosophy of widening access to higher education is explained. He is an ardent advocate of widening access to higher education in Uganda. The implication of widening access to higher education and development through research is assessed.